Enhancing students' writing paragraphs through Canva Magic AI - Utami, Silvia; Karnedi, Karnedi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2024)
This research aimed to investigate the influence of Canva Magic AI on improving students' writing quality and to gauge their perceptions of using the tool. The study utilized a quantitative, pre-experimental One-Group Pretest–Posttest Design. Eight English literature students were selected using convenience sampling from an Intermediate English Grammar and Paragraph Writing class at STBA Persada Bunda during the 2023-2024 academic year. Data were collected via a writing test and a questionnaire. The findings revealed a significant improvement in students' writing quality after using Canva Magic AI, with a p-value of 0.012 from the Wilcoxon signed-rank test. Notable enhancements were observed across various writing components, including better organization, with more students receiving "Excellent to Good" ratings and the complete elimination of the "Not College Level Work" category.  Logical development of ideas component showed significant improvement, with more students achieving higher ratings and lower ratings decreasing to zero. Grammar quality also improved markedly, with increases in higher ratings and decreases in lower ones. Progress was observed in punctuation, spelling, mechanics, and the style and quality of expression, with significant boosts in higher ratings and reductions in lower performance levels. Furthermore, students' perceptions of Canva Magic AI were highly positive, with mean ratings consistently above 4.0 on a 5-point scale. They acknowledged the tool's effectiveness in improving their writing skills and content creation, although some reported variability in experiences with errors, indicating a need for further refinement. The research underscores the effectiveness of Canva Magic AI as a supplementary educational tool, demonstrating its potential to enhance writing skills and overall quality. The implications for educational practices suggest integrating AI tools like Canva Magic AI into curricula to support and improve students' writing proficiency,  fostering a more engaging and efficient learning environment.